2020
DOI: 10.1371/journal.pone.0231614
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of XEN®—Implantation vs. trabeculectomy: Data of a “real-world” setting

Abstract: ObjectiveTo compare surgical success, postoperative intraocular pressure and complication rates between trabeculectomy and XEN gelstent surgery in a cohort of glaucoma patients in a typical clinical setting. MethodsA retrospective cohort study of consecutive patients with refractory open-angle glaucoma including patients who underwent either stand-alone XEN gelstent insertion with Mitomycin C or trabeculectomy with Mitomycin C between 2016 and 2018 at the University Eye Hospital Mainz, Germany. Primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 23 publications
(27 reference statements)
9
75
2
7
Order By: Relevance
“… 18 , 21 , 22 , 23 , 24 , 37 , 38 , 39 , 40 , 41 Direct comparison of ab interno XEN Gel Stent implantation with trabeculectomy in POAG patients found no difference in the rates of surgical success or reduction in IOP lowering medications. 24 , 39 , 42 , 43 While one study found that trabeculectomy resulted in lower postoperative IOPs, 39 others found no difference. 42 , 43 Patients receiving XEN Gel Stents benefited from fewer postoperative visits and a faster postoperative course.…”
Section: Discussionmentioning
confidence: 98%
“… 18 , 21 , 22 , 23 , 24 , 37 , 38 , 39 , 40 , 41 Direct comparison of ab interno XEN Gel Stent implantation with trabeculectomy in POAG patients found no difference in the rates of surgical success or reduction in IOP lowering medications. 24 , 39 , 42 , 43 While one study found that trabeculectomy resulted in lower postoperative IOPs, 39 others found no difference. 42 , 43 Patients receiving XEN Gel Stents benefited from fewer postoperative visits and a faster postoperative course.…”
Section: Discussionmentioning
confidence: 98%
“…The indication whether to perform TET or XEN microstent implantation was defined when the XEN microstent was first introduced to our clinic, which was before the actual retrospective study was designed. The indications relied on the following assumptions: The XEN microstent was developed as a minimally invasive procedure with the goal to generate comparable postoperative results to those after TET in terms of IOP reduction 18 20 . The XEN microstent is implanted using an ab interno approach.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an IOP reduction at 12-month follow-up of 7.2 ± 8.2 mmHg in the XEN group and 10.5 ± 9.2 mmHg in the trabeculectomy group were observed from baseline values of 19.0 mmHg (95%CI: 16.8-25.0 mmHg) and 21.0 mmHg (95%CI: 17.0-27.0 mmHg), respectively (P = 0.003). Medication reduction was also reduced to 0.3 ± 0.5 and 0.2 ± 0.4 in the XEN and trabeculectomy cohorts, respectively from baseline values of 2.0 (95%CI: 1.0-3.0) and 3.0 (95 CI: 2.0-4.0), respectively [23] .…”
Section: Xen: Mechanism Of Action and Effectivenessmentioning
confidence: 83%
“…Key statistics on mechanism of action, effectiveness, and safety profile were extracted for each type of MIGS (an overview of these findings summarised in Table 2). Analysed procedures were limited to Schlemm's canal iStent Hooshmand et al [5] Ferguson et al [6] Ferguson et al [7] Ahmed et al [8] Katz et al [9] + Hooshmand et al [5] Samuelson et al [10] + CE + CE Samuelson et al [4] Ahmed et al [8] + CE + CE Davids et al [11] Heersink et al [12] +/-CE Esfandiari et al [13] Avar et al [14] + CE +/-CE Elmallah et al [16] + CE RCS 315 eyes 12 mo: -27.47 12 mo: -1.03 Supraciliary space/ciliary process CyPass Vold et al [17] Reiss et al [18] Fard et al [19] Fard et al [19] + Myers et al [20] + 2 iStent PCS 80 subjects 48 mo: -41.36 n/a ECP Pantalon et al [21] + CE + 2 iStent PCS 63 eyes 12 mo: -34.65 12 mo: -0.98 Subconjunctival space XEN Gel Stent Olgun et al [15] Karimi et al [22] Wagner et al [23] Gillmann et al [24] +…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation